Hepatocellular carcinoma with right atrial tumor thrombus - Guo, Yi-Xian (Zeitschrift für Gastroenterologie, 2020)
Background Hepatocellular carcinoma with right atrial tumor thrombus is uncommon but with a dismal prognosis.Methods By comprehensive retrieval of literature published between 2000 and 2019, 53 reports were obtained with 187 patients recruited into this study. The extracted data included patient characteristics, tumor characteristics, treatment, follow-up and outcomes. Statistical analyses applied were student t, Fisher exact and I2 tests. Patients were devided into 6 groups according to treatment of choices: transarterial chemoembolization (TACE), surgery, radiotherapy, chemotherapy, interventional treatment and supportive care.Results The overall survival rate of this cohort was 40.8 %. The survival rate of patients receiving TACE was 33.3 % and that of surgical patients was 41.9 %. The survival time of patients with TACE was longer than surgical patients, but lack of a statistical significance. Patients had a follow-up of 15.7 ± 16.6 (median 10) months. The patients receiving radiotherapy had the longest follow-up among all groups. Intra- and/or extrahepatic recurrence of hepatocellular carcinoma was the major morbidity. The mortality rates in a decremental sequence for patients receiving different treatments were supportive care > radiotherapy > surgery > TACE > interventional treatment. No difference was found in mortality between patients reported from case reports and those from non-case reports.Conclusions Advanced hepatocellular carcinoma with right atrial thrombus is an aggressive malignancy. Based on the results of median survival time, radiotherapy and TACE seemed to be associated with an improved prognosis and possible better survival.
Keywords: hepatocellular carcinoma; right atrium; tumor thrombi; thalidomide